A New Paradigm of Competition Law in Indonesia - Pranoto, Azan; Tarmizi; Isnainul, OK (Angstrom Centre of Education, 2025)
Competition law is a combination of two opposing ideologies: ethatism, which promotes state ownership and control over private enterprise, and Free Fight liberalism, which supports unrestricted free competition. As a highly dynamic period develops, laws must be able to address these issues, particularly the conditions of the Indonesian state, by implementing economic theories that serve as the foundation for social life-sustaining politics and laws. For the purpose to stop the cartel phenomena, we utilize applicable rules known as Undang-undang No. 5 Tahun 1999 tentang Larangan Praktek Kartel monopoli dan persaingan usaha tidak sehat (Regulation No. 5/1999 on Prohibition of Cartel Monopolistic Practices and Unfair Business Competition) and normative juridical on the creation of competition legislation in this research. We next examine the prospects and difficulties associated with the cartel phenomena in Indonesia using a new paradigm. As a result, our goal is to adding articles to the competition law regulations on the cartel issue.